(untitled) - Hoang, Phi Long (Netherlands, 2017)
This multidisciplinary study focuses on projecting and adapting to future hydrological changes in the Mekong – an international river of global significance in terms of rapidly increasing human pressures and climate-change vulnerability. A modelling framework was developed to project future changes in both the river flow regime and hydrological extremes (i.e. high/low flows and floods), under multiple scenarios of climate change, irrigation and hydropower developments. Furthermore, we developed a combined quantitative-qualitative approach to develop suitable adaptation measures and strategies to future floods in the Mekong Delta being a key vulnerability hotspot.
Keywords: Quản lý chất lượng nước,Water quality management